THE EFFECTIVENESS OF USING TEAM ASSISTED INDIVIDUALIZATION TECHNIQUE ON THE STUDENTâS ACHIEVEMENT OF SIMPLE PAST TENSE - Hamidah, Luluk Nur; Rahayu, Nanik Sri (Pusat Pengembangan Bahasa, 2016)
Grammar is the description of the ways in which words are formed and can change their form and can be combined into sentences in order to express different meanings.The students need ability how to have a good grammar especially in simple past tense. Simple past tense is the form of a verb used to describe actions in the past. After knowing the highly complex grammar especially in simple past tense, teacher needs to move to how to select the materials and activities to be used in grammar class. One of techniques used in teaching grammar is Team Assisted Individualization technique, Team Assisted Individualization technique belongs to the cooperative learning. Team Assisted Individualization technique is a technique in which the students are placed into the small groups and then followed by the giving the help individually for the student who need it. The score âtâ at the signifcance level of 5%, the calculation t-count is 9.49, and the value of âtâ on the t-table with the signifcance 5% with the value of Df = 50, it can be found that t-table = 2.01. It means that there is difference grammar score between experimental and control class. Based on the explanation above, the Team Assisted Individualization technique surely shows the real effectiveness.